2014
DOI: 10.1016/j.immuni.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis via Standardized Whole-Blood Stimulation Systems Defines the Boundaries of a Healthy Immune Response to Complex Stimuli

Abstract: Standardization of immunophenotyping procedures has become a high priority. We have developed a suite of whole-blood, syringe-based assay systems that can be used to reproducibly assess induced innate or adaptive immune responses. By eliminating preanalytical errors associated with immune monitoring, we have defined the protein signatures induced by (1) medically relevant bacteria, fungi, and viruses; (2) agonists specific for defined host sensors; (3) clinically employed cytokines; and (4) activators of T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
229
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 204 publications
(246 citation statements)
references
References 86 publications
8
229
1
5
Order By: Relevance
“…As has been previously reported, the selection of anti-coagulant may significantly impact the accuracy of whole blood-based diagnostic tests for hematologic disease since different anti-coagulants have varying effects on blood cells for immunophenotying, morphology or other parameters [28] . Indeed, in a recent publication by Duffy et al [29] where multiple stimuli were used in a human whole blood assay to standardize stimulation systems and define boundaries of a healthy human immune response, the three anticoagulants used herein were also tested. Duffy and colleagues also found that activation by a multiplicity of stimuli, including bacterial, viral, cytokine, TCR and microbial-associated molecular patterns (MAMP) were optimally achieved when blood was collected in heparinized tubes.…”
Section: Optimization Of Monocyte Activationmentioning
confidence: 99%
“…As has been previously reported, the selection of anti-coagulant may significantly impact the accuracy of whole blood-based diagnostic tests for hematologic disease since different anti-coagulants have varying effects on blood cells for immunophenotying, morphology or other parameters [28] . Indeed, in a recent publication by Duffy et al [29] where multiple stimuli were used in a human whole blood assay to standardize stimulation systems and define boundaries of a healthy human immune response, the three anticoagulants used herein were also tested. Duffy and colleagues also found that activation by a multiplicity of stimuli, including bacterial, viral, cytokine, TCR and microbial-associated molecular patterns (MAMP) were optimally achieved when blood was collected in heparinized tubes.…”
Section: Optimization Of Monocyte Activationmentioning
confidence: 99%
“…SEB has been used as a T-cell superantigen and provides useful information on T-cell signaling pathways; however, anti-CD3/28 MAb stimulation is considered to be a more physiologically relevant mode of in vivo T-cell activation than SEB (42,43). Anti-CD3/28 MAbs and SEB stimulate T cells by inducing TCR signaling and by cross-linking of major histocompatibility complex class II (MHCII) and the TCR, respectively (44)(45)(46).…”
Section: Dynamics Of Individual Cytokine/chemokine Responses In Cd4mentioning
confidence: 99%
“…The integrated epigenetic profiles can then be used as a priori information to help identifying causal SNPs and delineate the mechanistic basis of inter-individual differences in immune response. Although the studies discussed herein have primarily focused on transcriptional responses of coding genes and on innate immunity, we expect in the upcoming years to see the integrative use of in vitro immunological assays with genetic and epigenetic information to be applied to other immunological-related endophenotypes (e.g., stimuli-induced cytokine and chemokine levels [13]), to the study of the genetic regulation of immune-associated microRNAs [65] and long noncoding RNAs, as well as to the study of the mechanistic basis of heterogeneity in adaptive immune responses [11]. Results from these studies will provide a foundation for defining the primary factors leading to perturbations in an individual's immune responses, thus making it possible to devise personalized therapeutic regimes in a more informed manner.…”
Section: Resultsmentioning
confidence: 99%